Comprehensive analysis of metabolomics on flesh quality of yellow catfish (Pelteobagrus fulvidraco) fed plant-based protein diet - Li, Xue; Wang, Shidong; Zhang, Muzi; Jiang, Haibo; Qian, Yunxia; Wang, Rixin; Li, Ming (Frontiers in Nutrition, 2023)
Plant protein components have been evidenced to have an impact on the flesh quality and flavor of freshwater fish. However, few studies have concentrated on the potential mechanisms involved. In this study, a combination of metabolomics and gene expression analysis was used to investigate the effects of plant protein components on flesh quality and flavor of yellow catfish. A total of 540 yellow catfish, with an initial average body weight of 1.67 ± 0.27 g, were randomly allotted into six experimental groups with three replicates each, and respectively fed six different diets for 8 weeks. The results showed that replacement of fish meal with cottonseed meal (CM), sesame meal (SEM) and corn gluten meal (CGM) in the diet significantly reduced growth performance, crude protein, crude lipid, but the flesh texture (hardness and chewiness) were observably increased. Moreover, the flavor-related amino acid (glutamic acid, glycine, and proline) contents in CM, SEM, and CGM group of yellow catfish muscle were significantly increased compared with fish meal group. Metabolomic data showed that soybean meal (SBM), peanut meal (PM), CM, SEM, and CGM mainly regulated muscle protein biosynthesis by vitamin B6 metabolism, proline metabolism, glutamic acid metabolism, phenylalanine, and tyrosine metabolism, respectively. Correlation analysis between metabolomic data and gene expression suggested that SBM, CM, PM, SEM, and CGM primarily regulated the mRNA level of muscle proliferation related genes by arginine, glutamic acid, phenylalanine, and tyrosine metabolism, respectively.